Development of Traditional Parmayaman-Based Digital Flifbooks in Increasing Scientific Literacy in the Disruptive Era - Nirwana Anas; Ahmad Tarmizi Hasibuan (Postgraduate, University of Mataram, 2023)
The Covid 19 outbreak has reduced elementary age children's interest in reading, especially in the field of science. This becomes a problem, which makes education practitioners to make online learning interesting and fun. Digital Flipbook media is a